Environmental effects of tilapia (Oreochromis nilotica L.) and artificial feeding on phytoplankton and fish yield in polyculture ponds - Rahman, Mohammad Mustafizur; Verdegem, Marc C.J.; Wahab, Md Abdul; Hossain, M. Y.; Jo, Qtae; Gong, Yeong (2008)
In south Asia, most indigenous carp species rely mostly on natural food and therefore these species are commonly cultured in semi-intensive polyculture system. Generally, a combination of 5-8 species is stocked and most of the cases farmers are very disappointed due to slow growth rate of fish. However, they do not understand the real cause and complain about the complexity of managing many species in a culture system. Therefore, nowadays farmers have a tendency to use fewer species. Experimental manipulation of stocking densities suggest greater yields and comparatively better water quality occur when 1.5 rohu (Labeo rohita) are cultured with 0.5 common carp (Cyprinus carpio) per m2. To increase further fish production using limited resource and by exploiting excess natural food, addition of tilapia (Oreochromis nilotica) in low density (0.2 m-2) was suggested. Therefore, the aim of the present study was to know the effects of tilapia addition on pond environment and its effects on phytoplankton and fish growth in rohu-common carp polyculture system. Artificially fed and non-fed ponds were also compared. The 4.5-months experiment was carried out at the Bangladesh Agricultural University. Four treatments, randomly assigned and in triplicate, were compared: 1.5 rohu plus 0.5 common carp m-2 without (treatment 0T) and with artificial feed (0T-F), and 1.5 rohu plus 0.5 common carp plus 0.2 tilapia m-2 without (T) and with artificial feed (T-F). The results showed that NO3-N, total ammonia-nitrogen (TAN), total nitrogen (TN), PO4-P and total phosphorous (TP) concentrations were greater (P<0.05) in tilapia ponds than the ponds without tilapia. The opposite results were observed in case of Chlorophyll-a (Chl-a) and TSS due to tilapias high grazing pressure on phytoplankton. Artificial feeding lowered DO, total alkalinity and transparency of water, whereas the opposite results were observed in case of NO3-N, TAN, TN, PO4-P, TP, TSS and Chl-a concentrations. Tilapia decreased the effects of artificial feed on Chl-a (Fig. 1) and TSS concentrations. Tilapia had no significant effect on any yield parameter of rohu and common carp. All yield parameters of rohu, common carp and tilapia were better (P<0.01) in fed than non-fed ponds. Combined effects of tilapia addition and artificial feed resulted highest total net fish yield in treatment T-F (P<0.05) (Fig. 2). Therefore, a combination of 1.5 rohu plus 0.5 common carp plus 0.2 tilapia m-2 with artificial feed may be used for polyculture farmers in south Asian region.